2010
DOI: 10.1051/0004-6361/201014419
|View full text |Cite
|
Sign up to set email alerts
|

The magnetically-active, low-mass, triple system WDS 19312+3607

Abstract: Aims. We investigated in detail the system WDS 19312+3607, whose primary is an active M4.5Ve star previously inferred to be young (τ ∼ 300-500 Ma) based on its high X-ray luminosity. Methods. We collected intermediate-and low-resolution optical spectra taken with 2 m-class telescopes, photometric data from the B to 8 μm bands, and data for eleven astrometric epochs with a time baseline of over 56 years for the two components in the system, G 125-15 and G 125-14. Results. We derived the M4.5V spectral types of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…I19312+3607 itself is noted as a very close (<0.01 AU) double-lined spectroscopic binary in Shkolnik et al (2010). Additionally, there is a wide common proper motion companion at 46 ′′ (Caballero 2010).…”
Section: I18427+1354 (Gj 4071)mentioning
confidence: 96%
“…I19312+3607 itself is noted as a very close (<0.01 AU) double-lined spectroscopic binary in Shkolnik et al (2010). Additionally, there is a wide common proper motion companion at 46 ′′ (Caballero 2010).…”
Section: I18427+1354 (Gj 4071)mentioning
confidence: 96%
“…Most prominently, the level of stellar activity may cause such a bias. For example, Caballero et al (2010), Jackson et al (2018), and Kesseli et al (2018) reported inflated radii for young, magnetically active, or fast rotating stars.…”
Section: Introductionmentioning
confidence: 99%
“…Spectropolarimetry is conducted in combination with the grisms 400 Å/mm, 200 Å/mm, and 100 Å/mm. Apart from GRB follow-ups, CAFOS is contributing to SNe [242], binary star [243], and galaxy studies.…”
Section: Caha/cafosmentioning
confidence: 99%